Réponses

2014-03-02T10:35:21+01:00
Bonjour

√3(2 - 5√3) = 2√3 - 5√3 * √3
                   = 2√3 - 5 * 3
                   = 2√3 - 15

5√2(√2 - 7√18) = 5√2 * √2 - 5√2*7√18
                         = 5 * 2 - 5*7√36
                         = 10 - 35*6
                         = 10 - 210
                         = -200

(√6 + 2)√2 = √6 * √2 + 2√2
                  = √12 + 2√2
                  = √(4*3) + 2√2
                  = √4 * √3 + 2√2
                  = 2√3 + 2√2

2√12(√12 - √3 + √6) = 2√12*√12 - 2√12*√3 + 2√12*√6
                                 = 2 * 12 - 2√36 + 2√72
                                 = 24 - 2 * 6  + 2√(36*2)
                                 = 24 - 12 + 2 √36*√2
                                 = 12 + 2* 6*√2
                                 = 12 + 12√2
le * c koi
C'est le signe de la multiplication.
ok merci